Endometriosis: A Rare Cause of Large Bowel Obstruction. - Alexandrino, G (2018)
Large bowel obstruction can result in significant morbidity and mortality, especially in cases of acute complete obstruction. There are many possible causes, the most common in adults being colorectal cancer. Endometriosis is a benign disease, and the most affected extragenital location is the bowel, especially the rectosigmoid junction. However, transmural involvement and acute occlusion are very rare events. We report an exceptional case of acute large bowel obstruction as the initial presentation of endometriosis. The differential diagnosis of colorectal carcinoma may be challenging, and this case emphasizes the need to consider intestinal endometriosis in females at a fertile age presenting with gastrointestinal symptoms and an intestinal mass causing complete large bowel obstruction.